Critical Chemical-Quality Assessment for the Oxidative Stability of Bulk Palm Oil in Indonesia - Drajat Martianto; Nuri Andarwulan; Donald Siahaan; Desty Gitapratiwi; Ria Noviar Triana; Purwiyatno Hariyadi (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2018)
The main objective of this study was to assess the quality of bulk palm oil from the point of production (and its distributors) using the critical factors of vitamin A stability and carotenoids (expressed as beta-carotene) in Indonesia. The specific objectives were to analyze the peroxide value (PV), acid value of free fatty acid (FFA) and carotenoids (expressed as beta-carotene) content of unfortified bulk palm oil in Indonesia. The study showed that the quality of initial bulk palm cooking oil, both at the level of manufacturers and distributors, was inconsistent; however, it was still in compliance with the Indonesian standard for cooking oil (SNI 7709-2012). The PV and FFA range of bulk palm cooking oil analyzed was 0-8.94 meq O2 kg-1 and 0.06-0.23% respectively, and the range of carotenoids content (expressed as beta-carotene) was quite low, only 1.2-3.05 ppm, respectively. The results of this study could be used as the basis of vitamin A fortification in palm oil, since the stability of the fortificant in the oil would be affected by the initial chemical quality, especially its FFA and PV content